2022
DOI: 10.3390/molecules27248857
|View full text |Cite
|
Sign up to set email alerts
|

Application of Maillard Reaction Products Derived Only from Enzymatically Hydrolyzed Sesame Meal to Enhance the Flavor and Oxidative Stability of Sesame Oil

Abstract: The low-temperature roasting of sesame oil has become increasingly popular because of its nutritional benefits; however, the flavor is reduced. In order to improve the quality of sesame oil without exogenous addition, sesame meal was hydrolyzed and further used to prepare Maillard reaction products (MRPs) while protease hydrolysis (PH) and glucoamylase-protease hydrolysis (GPH) were used, and their respective Maillard products (PHM and GPHM) were added in the oils for reducing sugar and total sugar content det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Seven Pyrazine compounds with OAVs ≥ 1 were screened from the yellow horn seed oil, including 2,5-dimethylpyrazine (roasted, nutty, popcorn), 2-mthyl-6-methylpyrazine (roasted, baked potato), 2,3,5-trimethylpyrazine (roasted, nutty), 3-ethyl-2,5-dimethylpyrazine (roasted, nutty), 2-ethyl-3,5-dimethylpyrazine (nutty, roasted, sweet), 2,6-diethylpyrazine (roasted, nutty, sweet), and 2,3-diethyl-5-methylpyrazine (raw peanut, potato). 2, 6-diethylpyrazine, an important product of the Maillard reaction [51], has been identified as a key aroma compound in sesame oil [11] and virgin rapeseed oil [52], providing nutty and toasty profiles. The results suggest that the presence of these aroma compounds contributes to the development of a nuanced roasted and nutty aroma in yellow horn seed oil.…”
Section: Gc-o-ms Analysis 321 Volatile Compounds Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Seven Pyrazine compounds with OAVs ≥ 1 were screened from the yellow horn seed oil, including 2,5-dimethylpyrazine (roasted, nutty, popcorn), 2-mthyl-6-methylpyrazine (roasted, baked potato), 2,3,5-trimethylpyrazine (roasted, nutty), 3-ethyl-2,5-dimethylpyrazine (roasted, nutty), 2-ethyl-3,5-dimethylpyrazine (nutty, roasted, sweet), 2,6-diethylpyrazine (roasted, nutty, sweet), and 2,3-diethyl-5-methylpyrazine (raw peanut, potato). 2, 6-diethylpyrazine, an important product of the Maillard reaction [51], has been identified as a key aroma compound in sesame oil [11] and virgin rapeseed oil [52], providing nutty and toasty profiles. The results suggest that the presence of these aroma compounds contributes to the development of a nuanced roasted and nutty aroma in yellow horn seed oil.…”
Section: Gc-o-ms Analysis 321 Volatile Compounds Analysismentioning
confidence: 99%
“…In the current process of plant oil production, raw materials are typically subjected to elevated temperatures of roasting prior to pressing to increase oil yield and enhance aroma [9]. Properly executed high-temperature roasting can enrich oils with aromatic substances through a series of reactions such as the Maillard reaction, lipid oxidation, Strecker degradation and caramelization [10], which generate a variety of aroma substances, including aldehydes, alcohols, and pyrazines [11].…”
Section: Introductionmentioning
confidence: 99%
“…The type of reducing sugar and amino acid is the main factor influencing the formation of various flavors. Previous studies have focused on the formation mechanism and flavor presentation of different classes of reducing sugars and amino acids in the MR. For example, Ma concluded that the MR between histidine and glucose generates numerous pyrazine flavoring substances that contribute significantly to the flavor of sesame oil( Ma et al, 2022 ). Zou( Zou, Gao, He, & Yang, 2018 )investigated the effect of bioproducts from the MR between reducing sugars and primary amino acids in the volatile composition of wheat germ oil during roasting.…”
Section: Introductionmentioning
confidence: 99%